A good combination of strength and ductility of ultra-coarse-grained Cu-Al alloy with coarse-grained surface layer via pre-torsional treatment. (February 2020) - Gong, Yanli; Gu, Ji; Ni, Song; Wu, Hong; Song, Min
Graphical abstract: Highlights: An ultra-coarse-grained (UCG) Cu-6 wt.%Al alloy with a coarse-grained (CG) surface layer was fabricated by surface mechanical attrition treatment. Gradient microstructures were formed after pre-torsional treatment. The strength and ductility can be simultaneously enhanced via pre-torsional deformation due to the formation of gradient microstructures. Abstract: The trade-off between strength and ductility is a long-standing dilemma in metals and alloys. In this study, we fabricated an ultra-coarse-grained (UCG) Cu-6 wt.%Al alloy with a coarse-grained (CG) surface layer by surface mechanical attrition treatment. Pre-torsional treatment for 45°, 90° and 180° was conducted on the UCG-CG specimens, and the effects of pre-torsional treatment on the microstructures and mechanical properties of the UCG-CG Cu-6 wt.%Al alloy were systematic investigated. It has been shown that the strength and ductility can be simultaneously enhanced via pre-torsional deformation due to the formation of gradient microstructures.